2017
DOI: 10.17265/2328-2150/2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heart Rate Variability in Allergic and Highly Trait Anxious Individuals

Abstract: Autonomic dysregulations were repeatedly observed in people with allergic reactions. Contradictory results of sympathetic over-activation on one hand and parasympathetic predominance on the other, were described for both atopic dermatitis and allergic rhinitis. Secondly, psychological traits of high anxiety and depression described in allergic patients are mostly associated with increased sympathetic and decreased vagal modulation. To address inconsistency in prior findings, we aim to study autonomic nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…There is a limited number of epidemiological studies of allergic populations, which have shown mixed results (43,44). However, these studies predominantly suggest higher parasympathetic (45)(46)(47)(48) and lower sympathetic (43,(47)(48)(49)(50) activity when compared to non-allergic controls. It has been proposed that decreased sympathetic activity can lead to a pro-inflammatory state in other organ systems (42), of interest to measured health outcomes beyond the upper respiratory tract.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…There is a limited number of epidemiological studies of allergic populations, which have shown mixed results (43,44). However, these studies predominantly suggest higher parasympathetic (45)(46)(47)(48) and lower sympathetic (43,(47)(48)(49)(50) activity when compared to non-allergic controls. It has been proposed that decreased sympathetic activity can lead to a pro-inflammatory state in other organ systems (42), of interest to measured health outcomes beyond the upper respiratory tract.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%